Genotype-Phenotype Correlation of Maternally Inherited Disorders due to Mutations in Mitochondrial DNA - Peterus Thajeb; Daofu Dai; Ming-Fu Chiang; Woei-Cherng Shyu (Elsevier, 2006)
Mitochondrial disorders are heterogeneous systemic ailments that are most often caused by maternal inheritance of a variety of mutations of the mitochondrial (mt) DNA. Paternal inheritance and somatic mutation are rare. The disorders are well recognized not only for the genotypic heterogeneity, but also the phenotypic variation among the affected members of a single family. The genotype-phenotype correlation of the diversity of the syndromic and non-syndromic features of mitochondrial disorders are discussed. Some aspects of the molecular mechanisms of this heterogeneity, and the histopathologic findings are highlighted.